Peningkatan Hasil Belajar Matematika melalui Pendekatan Pembelajaran Problem Base Learning (PBL) Secara Daring Dan Pemberian Tugas Terstruktur Pada Siswa Kelas X SMA Al-Anwar Bina Mulya - Ahmad Fahrudin (Peneliti.net, 2021)
The research design used by the researcher is Classroom Action Research (CAR) in online activities. The subjects in this study were students and mathematics teachers of class X SMA Al-Anwar Bina Mulya. The results of the first cycle evaluation test have not been achieved because they are not in accordance with the expected success indicators. There are 12 students who get a score of 75 or complete learning, while those who do not finish studying are 7 students with an average score of 73.68 with a standard deviation of 7.42. While the results of the second cycle evaluation test showed that there were 17 students who got a score of 75 or completed learning and 2 students who did not complete their studies with an average score of 81.31 the percentage of students who finished studying was 89% so that they met the criteria for success indicators even though Thus, this research was continued to cycle III to find out whether the success of cycle III was the same as cycle II. In the third cycle of students who got a score of 75 or completed learning there were 19 students with an average score of 82.63 with a percentage of the number of students who finished learning 100% so it can be said that the results of the third cycle increased from the second cycle. From the research results, it can be concluded that the provision of structured assignments with feedback can improve the learning outcomes of class X Semester II students of SMA Al-Anwar Bina Mulya which is located at Jl. North Parimeter Kp. Crackle etc. Bird Swamp District. Kosambi Tangerang Regency. The research subject of this research is class X SMA Al-Anwar Bina Mulya, totaling 19 students, consisting of 5 male students and 14 female students